Habilidades sociais, empatia, amor e satisfação no ciclo vital familiar - BARROS, Roberta de Souza Nogueira; SOARES, Adriana Benevides; HERNANDEZ, José Augusto Evangelho (Estudos de Psicologia (Campinas), 2023)
This study verifi ed the predictive relationships between social skills, beliefs about love and marital satisfaction in the family life cycle. The participants of this study were 446 married adults, of both sexes, living in the metropolitan area of the city of Rio de Janeiro, Brazil. The explanatory variables that contributed most to the marital satisfaction of men were passion, proactive self-control, decision/commitment, and for women they were commitment, affective sensitivity, decision/ commitment, and passion. It was concluded that the dimensions related to love constructs were more explanatory of marital satisfaction, except at the stage of couples with small children whose social skills were more prominent. These results may contribute to preparatory programs and therapies related to marital life.